Active Commuting: Workplace Health Promotion for Improved Employee Well-Being and Organizational Behavior - Page, Nadine C.; Nilsson, Viktor O. (Frontiers in Psychology, 2017)
Objective: This paper describes a behaviour change intervention that encourages active commuting using electrically assisted bikes (e-bikes) for health promotion in the workplace. This paper presents the preliminary findings of the intervention’s impact on improving employee wellbeing and organisational behaviour, as an indicator of potential business success. Method: Employees of a UK-based organisation participated in a workplace travel behaviour change intervention and used e-bikes as an active commuting mode; this was a change to their usual passive commuting behaviour. The purpose of the intervention was to develop employee wellbeing and organisational behaviour for improved business success. We explored the personal benefits and organisational co-benefits of active commuting and compared these to a travel-as-usual group of employees who did not change their behaviour and continued taking non-active commutes. Results: Employees who changed their behaviour to active commuting reported more positive affect, better physical health and more productive organisational behaviour outcomes compared with passive commuters. In addition, there was an interactive effect of commuting mode and commuting distance: a more frequent active commute was positively associated with more productive organisational behaviour and stronger overall positive employee wellbeing whereas a longer passive commute was associated with poorer wellbeing, although there was no impact on organisational behaviour. Conclusions: This research provides emerging evidence of the value of an innovative workplace health promotion initiatives focused on active commuting in protecting and improving employee wellbeing and organisational behaviour for stronger business performance. It considers the significant opportunities for organisations pursuing improved workforce wellbeing, both in terms of employee health, and for improved organisational behaviour and business success.